miR390, Arabidopsis TAS3 tasiRNAs, and their AUXIN RESPONSE FACTOR targets define an autoregulatory network quantitatively regulating lateral root growth - Marin, Elena; Jouannet, Virginie; Maizel, Alexis (The plant cell, 2010)
Plants adapt to different environmental conditions by constantly forming new organs in response to morphogenetic signals. Lateral roots branch from the main root in response to local auxin maxima. How a local auxin maximum translates into a robust pattern of gene activation ensuring the proper growth of the newly formed lateral root is largely unknown. Here, we demonstrate that miR390, TAS3-derived trans-acting short-interfering RNAs (tasiRNAs), and AUXIN RESPONSE FACTORS (ARFs) form an auxin-responsive regulatory network controlling lateral root growth. Spatial expression analysis using reporter gene fusions, tasi/miRNA sensors, and mutant analysis showed that miR390 is specifically expressed at the sites of lateral root initiation where it triggers the biogenesis of tasiRNAs. These tasiRNAs inhibit ARF2, ARF3, and ARF4, thus releasing repression of lateral root growth. In addition, ARF2, ARF3, and ARF4 affect auxin-induced miR390 accumulation. Positive and negative feedback regulation of miR390 by ARF2, ARF3, and ARF4 thus ensures the proper definition of the miR390 expression pattern. This regulatory network maintains ARF expression in a concentration range optimal for specifying the timing of lateral root growth, a function similar to its activity during leaf development. These results also show how small regulatory RNAs integrate with auxin signaling to quantitatively regulate organ growth during development.